Hinduism Contextual Learning In Elementary School - I Ketut Sudarsana (Purwadita : Jurnal Agama dan Budaya, 2020)
The purpose of this study was to find out the application of contextual learning in Hinduism subject in elementary school. The ability of teachers to create quality learning largely determines overall educational success. The quality of learning depends on the strength of teachers, especially in providing ease of learning to students effectively and efficiently. Contextual learning or often abbreviated as CTL is one learning strategy that can streamline the teaching and learning process where learning takes place naturally in the form of student work and experience activities, not just the transfer of knowledge from teacher to students, so learning is expected to be more meaningful for students.